Revision of the genus Athyreacarus (Acari: Athyreacaridae) - Khaustov, Alexander A.; Frolov, Andrey V. (Zootaxa, 2019)
Mites of the genus Athyreacarus (Acari: Athyreacaridae) associated with bolboceratine beetles (Coleoptera: Geotrupidae: Bolboceratine) of New World are revised, a new generic concept provided, and the family concept modified. Nine new species are described: A. grandis sp. nov. on Neoathyreus lanuginosus in Brazil; A. magnificus sp. nov. on Athyreus tuberifer in Brazil; A. variabilis sp. nov. on Neoathyreus cf. anthracinus in Brazil; A. similis sp. nov. on Neoathyreus centromaculatus in Bolivia; A. vazdemelloi sp. nov. on Parathyreus rectus in Brazil; A. pusillus sp. nov. on Athyreus brasilicus in Brazil; A. latus sp. nov. on Athyreus cf. bifurcatus from unknown locality; A. angustus sp. nov. on Bolbelasmus horni in USA; and A. ovalis sp. nov. on Bolbelasmus variabilis in Mexico. Bolbapium striatopunctatum, B. minutum, and B. sculpturatum are recorded as new phoretic host beetles for Athyreacarus primitivus. A key to genera and species of the family Athyreacaridae is provided.